Reunification and Re-entry to Care: An Analysis of the National Datasets for Children Looked after in England. (6th May 2022) - Goldacre, Allie; Hood, Rick; Jones, Ed; King, Adam; Wang, Chao
Abstract: This article reports on a quantitative study of the national datasets for children in state care in England. The aim of the study was to investigate the likelihood of re-entry to care for children who returned home to their parents or main carers after an episode of care. An anonymised extract of case-level information on all children who received an episode of care between 2014 and 2020 ( n  = 51, 238) was assembled from local authority (LA) administrative data held by the UK government. Cox regression models were used to calculate the cumulative probability of re-entry to care over time and identify the factors associated with a higher or lower probability. The findings showed that one in five children re-entered care after one year and over a third of children re-entered care after six years. A number of factors affected the probability of re-entering care, including age, ethnicity, care history, placement type and whether provision was LA, voluntary or private sector. Implications are discussed for planning and design of services to support reunification from care, and for the broader goal of reducing the number of children looked after by the state. Abstract : Summary in Plain English Children often return home to their parents after a period in care. However, this exit route is becoming less common and rates of re-entry to care following reunification are much higher than other routes to permanency. The likelihood of re-entry varies significantly depending on the type and quality of care provision. This has implications for practice and care planning for this important group of children and young people.